Relationship between Nutritional Status and Physical Freshness Levels with Learning Outcomes of Physical, Sports and Health Education - Djoni Rumondor; Christianti Anggraini Motto; Mareike Doherty Patras (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study aims to determine relationship between nutritional status and physical freshness levels with learning outcomes of physical, sports and health education. This research is a descriptive study with correlation techniques. This research is conducted at Junior High School I of Tondano, Sangihe Islands, North Sulawesi Province. Based on the results of research and discussion, some conclusions can be drawn as follows: 1) There is a relationship between nutritional status with learning outcomes of physical, sports and health education in Junior High School students I of Tondano; 2) There is a relationship between physical freshness with learning outcomes of physical, sports and health education in Junior High School students I of Tondano; 3) There is a relationship between nutritional status and physical freshness together with learning outcomes of physical, sports and health education in Junior High School students I of Tondano.